PROSPEK LPTK SWASTA MENGHADAPI KEBIJAKAN IMPLEMENTASI PENDIDIKAN PROFESI GURU (SEBUAH BOM WAKTU ) - -, Sutoyo (Widya Wacana: Jurnal Ilmiah, 2014)
The government has a strong comitment to increase the quality and welfare for teachers. Therefore, Pendidikan Profesi Guru program (Teachers Profession Education) is conducted by Lembaga Pendidik dan Tenaga Kependidikan both public and private which must be given permition by the government. This policy, however, is a time bomb because it still brings a high requirement in the implementation for private LPTK, especially for the quality Â and the academic position of the teachers. The quota for the participants is also limited by the government. Therefore for private LPTK which finds it difficult to meet the requirements will be left by the public. Key words: private LPTK, PPG, time bomb